A founder COL4A4 pathogenic variant resulting in autosomal recessive Alport syndrome accounts for most genetic kidney failure in Romani people - Plevova, Pavlina; Indrakova, Jana; Savige, Judy; Kuhnova, Petra; Tvrda, Petra; Cerna, Dita; Hilscherova, Sarka; Kudrejova, Monika; Polendova, Daniela; Jaklova, Radka; Langova, Martina; Jahnova, Helena; et al. (Frontiers in Medicine, 2023)
Introduction Romani people have a high prevalence of kidney failure. This study examined a Romani cohort for pathogenic variants in the COL4A3, COL4A4, and COL4A5 genes that are affected in Alport syndrome (AS), a common cause of genetic kidney disease, characterized by hematuria, proteinuria, end-stage kidney failure, hearing loss, and eye anomalies. Materials and methods The study included 57 Romani from different families with clinical features that suggested AS who underwent next-generation sequencing (NGS) of the COL4A3, COL4A4, and COL4A5 genes, and 83 family members. Results In total, 27 Romani (19%) had autosomal recessive AS caused by a homozygous pathogenic c.1598G>A, p.Gly533Asp variant in COL4A4 (n = 20) or a homozygous c.415G>C, p.Gly139Arg variant in COL4A3 (n = 7). For p.Gly533Asp, 12 (80%) had macroscopic hematuria, 12 (63%) developed end-stage kidney failure at a median age of 22 years, and 13 (67%) had hearing loss. For p.Gly139Arg, none had macroscopic hematuria (p = 0.023), three (50%) had end-stage kidney failure by a median age of 42 years (p = 0.653), and five (83%) had hearing loss (p = 0.367). The p.Gly533Asp variant was associated with a more severe phenotype than p.Gly139Arg, with an earlier age at end-stage kidney failure and more macroscopic hematuria. Microscopic hematuria was very common in heterozygotes with both p.Gly533Asp (91%) and p.Gly139Arg (92%). Conclusion These two founder variants contribute to the high prevalence of kidney failure in Czech Romani. The estimated population frequency of autosomal recessive AS from these variants and consanguinity by descent is at least 1:11,000 in Czech Romani. This corresponds to a population frequency of autosomal dominant AS from these two variants alone of 1%. Romani with persistent hematuria should be offered genetic testing.